2007
DOI: 10.1177/154405910708600709
|View full text |Cite
|
Sign up to set email alerts
|

Force-induced IL-8 from Periodontal Ligament Cells Requires IL-1β

Abstract: During orthodontic tooth movement, mechanical stresses induce inflammatory reactions in the periodontal ligament (PDL). We hypothesized that chemokines released from PDL cells under mechanical stress regulate osteoclastogenesis, and investigated the profiles and mechanisms of chemokine expression by human PDL cells in response to mechanical stress. In vitro, shear stress and pressure force rapidly increased the gene and protein expressions of IL-8/CXCL8 by PDL cells. Consistently, amounts of IL-8 in the gingiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 29 publications
2
29
0
Order By: Relevance
“…On the other hand, transient activation of p38 kinase in osteoblasts has been reported to be induced by cyclic stretch (Kusumi et al 2005), compression (Maeda et al 2007), fluid shear stress (Lee et al 2008;Yeh et al 2010), and magnetic force (Yuge et al 2003). Recent reports indicated that p38 activation is essential for Opg expression induced by cyclic stretch (Kusumi et al 2005), and compression-induce IL-8 expression (Maeda et al 2007). Intriguingly, acceleration of osteoblast differentiation induced by magnetic force is mainly attributed to p38 kinase activation, while the activity of ERKs or JNKs is dispensable (Yuge et al 2003).…”
Section: Jnks and P38 Kinasementioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, transient activation of p38 kinase in osteoblasts has been reported to be induced by cyclic stretch (Kusumi et al 2005), compression (Maeda et al 2007), fluid shear stress (Lee et al 2008;Yeh et al 2010), and magnetic force (Yuge et al 2003). Recent reports indicated that p38 activation is essential for Opg expression induced by cyclic stretch (Kusumi et al 2005), and compression-induce IL-8 expression (Maeda et al 2007). Intriguingly, acceleration of osteoblast differentiation induced by magnetic force is mainly attributed to p38 kinase activation, while the activity of ERKs or JNKs is dispensable (Yuge et al 2003).…”
Section: Jnks and P38 Kinasementioning
confidence: 99%
“…Transient activation of JNKs in osteoblasts has been reported to be induced by cyclic stretch (Danciu et al 2003), compression (Maeda et al 2007), and fluid shear stress (Lee et al 2008;. It has been reported that JNK activity is important for compressioninduced IL-8 expression (Maeda et al 2007).…”
Section: Jnks and P38 Kinasementioning
confidence: 99%
See 3 more Smart Citations